Pendidikan Islam: kaedah pengajaran & pembelajaran (Islamic education: teaching and learning methods) - Jasmi, Kamarul Azmi (Penerbit UTM, 2007)
Islam never marginalize the latest developments and technology to produce the best educational methods. However, teaching and learning (T&L) methods practiced by the Prophet should be the basis and reference. This is because Prophet is the best model that invites Muslims to practice the teachings of Islam and the Islamic morals. No doubt the success of T&L in Islamic Education and skills associated with the role of an effective teacher. Teaching basic skills to be mastered include the provision of teaching aids, conducting induction set, the application of creative and critical thinking, questioning skills, and handling classes for enrichment and recovery. Importance of Islamic Education encompasses reading, understanding, and memorizing verses of the Qur'an, faith, worship, Islamic morality, history, personalities, and civilization. Mastery and appreciation of all aspects of the student is able to develop a good human. Hopefully, this can serve as reading material, a guide and reference to the Islamic Education teachers in the school, teachers who are currently enrolled in Islamic education, the lecturers in institutes of higher education or college, and the entire staff of a religious teacher education as a vehicle to convey the message and teachings Islam in the Malay world.